EVALUATING HIGHER EDUCATION WEBSITE QUALITY USING WEBQUAL 4.0 AND IMPORTANCE PERFORMANCE ANALYSIS (IPA) (Jurnal Pilar Nusa Mandiri, 2024)
LLDikti Region III is a unit operating under the Ministry of Education, Culture, Research, and Technology, responsible for promoting the enhancement of higher education quality in Jakarta. One of the media used by LLDikti Region III to serve stakeholders is through its website; therefore, the quality of services on the website must be continuously enhanced. The aim of this research is to determine whether the LLDikti Region III website meets user expectations, measured using the Webqual 4.0 method and Importance-Performance Analysis (IPA). Usability, information quality, and service interaction quality that will be used to evaluate the quality of this website. The respondents consist of members of the academic community from universities within the LLDikti Region III. Data was collected through an online questionnaire using stratified sampling techniques with 165 respondents. The results of this study show that 54.9% of the website's quality affects user satisfaction, while the remainder is influenced by variables not tested in this study. Based on the analysis conducted using the IPA method, several indicators in quadrant I still require significant attention, as they are considered important by users but have low performance. From these findings, the researcher suggests developing the website in areas where performance is low, particularly for indicators in quadrant I.